A DESIGNED SCIENCE INQUIRY TRAINING PROGRAMME FOR PRE-PRIMARY TEACHERS IN NIGERIA - Ogieriakhi, Anne; Onyemowo, Felicia O; Ahmed, Usman (PUPIL: International Journal of Teaching, Education and Learning, 2020)
This paper examined pre-primary school teacher knowledge of inquiry teaching method, objectives of pre-primary education, the teaching of science in the pre-primary classroom, the importance of early childhood education designed and validated an inquiry science program for training the teachers, collection of data analysis of data and results. The study was carried out in Akwanga Local government Area of Nasarawa State Nigeria. It was guided by 3 research questions and one hypothesis. This study was an experimental study and the research design was a true experimental method, and it consisted of an experimental control group. The population was 82 teachers and the sample was of 20 teachers forming (20%) of the population was used. A sampling of the sample was by simple random (hat and draw by replacement) while the instrument was the teacher knowledge of inquiry-oriented Teaching Achievement test (TKITAT) and inquiry features observation checklist (IFOC). Descriptive statics was used to answer the research questions while the t-test was used to test the hypothesis. Results showed that 50% of the pre-primary teachers some level of knowledge on inquiry teaching method, 17% have 60% knowledge while 33 have 30% knowledge of inquiry teaching method and the type adopted mostly is observation 58% and demonstration method 60% in teaching: in testing the hypothesis, there was no significant difference between the experimental control group in the pre-test but after the training, the experimental group performed better 83.3% than the control group 35.5% and so the null hypothesis was rejected. It was therefore concluded that the designed science program for training the pre-primary teachers on the use of inquiry teaching methods was effective and some recommendations were put forward.